2014
DOI: 10.1038/srep04020
|View full text |Cite
|
Sign up to set email alerts
|

Rapid interferometric imaging of printed drug laden multilayer structures

Abstract: The developments in printing technologies allow fabrication of micron-size nano-layered delivery systems to personal specifications. In this study we fabricated layered polymer structures for drug-delivery into a microfluidic channel and aimed to interferometrically assure their topography and adherence to each other. We present a scanning white light interferometer (SWLI) method for quantitative assurance of the topography of the embedded structure. We determined rapidly in non-destructive manner the thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The impact of the structural accuracy and integrity of printed structures for different materials in the pharmaceutical context is relatively poorly understood. Sandler et al (12) used scanning white light interferometry (SWLI) to determine the thickness and roughness of films of printed excipients and drug/excipient mixtures. They also used the same technique to rapidly determine the structure and presence of defects in printed drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the structural accuracy and integrity of printed structures for different materials in the pharmaceutical context is relatively poorly understood. Sandler et al (12) used scanning white light interferometry (SWLI) to determine the thickness and roughness of films of printed excipients and drug/excipient mixtures. They also used the same technique to rapidly determine the structure and presence of defects in printed drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…, aesthetic quality of the tablet and the thickness of layer 91 deposition(Sandler et al, 2014a). More recently, a bench top 3D 92 printer was utilized to fabricate a bilayer tablet with immediate93 and extended release pattern(Khaled et al, 2014).…”
mentioning
confidence: 99%
“…However, the application of these techniques for solid state characterization of printed medicinal products has been reported for other medicinal compounds printed on different substrates, e.g., polytetrafluoroethylene (PTFE)‐coated fiberglass films 17. Moreover, the potential of imaging techniques for solid state characterization of printed medicinal products nowadays is widely being explored 8, 12, 16, 23. Hsu et al demonstrated implication of second‐order nonlinear optical imaging of chiral crystals (SONICC) for characterization of naproxen‐poly(vinylpyrrolidone) (PVP K‐90) solid dispersions prepared by the drop printing technique 16.…”
Section: Resultsmentioning
confidence: 99%
“…Hsu et al demonstrated implication of second‐order nonlinear optical imaging of chiral crystals (SONICC) for characterization of naproxen‐poly(vinylpyrrolidone) (PVP K‐90) solid dispersions prepared by the drop printing technique 16. Recently, Sandler et al have developed the scanning white light interferometer (SWLI) method for quantitative assurance of topography of printed medicinal products 23.…”
Section: Resultsmentioning
confidence: 99%